A single‐center retrospective study of pregnancy outcomes after emergency cerclage for cervical insufficiency. Issue 1 (6th July 2017) - Wang, Sheng; Feng, Ling
Abstract: Objective: To compare maternal and perinatal outcomes after emergency cerclage with those after elective cerclage. Methods: In a retrospective review, data were assessed from women with a viable singleton pregnancy who underwent elective or emergency cerclage for cervical insufficiency at the Tongji Hospital, Wuhan, China, between January 2010 and July 2015. Subgroup analyses based on cervical length (CL; ≤15, 15–25, and 25–30 mm) were also conducted among women undergoing emergency cerclage. Results: In total, 68 women underwent elective cerclage and 53 underwent emergency cerclage. The suture‐to‐delivery interval was significantly longer in the elective group (19.17 ± 5.86 weeks) than in the emergency group (11.29 ± 7.27 weeks; P< 0.001). There was no difference between the elective and emergency groups in mean pregnancy length at delivery, frequency of Apgar score below 7 at 5 minutes (live births only), or birth weight (live births only). An inverse trend in the degree of CL shortening with pregnancy outcomes was observed; women with a CL of 25–30 mm had the best outcomes. Conclusion: Pregnancy outcomes were similar after emergency and elective cerclage. There was an inverse trend in the degree of CL shortening with pregnancy outcomes in the emergency cerclage group, with better outcomes observed for women with longer CL. Abstract : Maternal and perinatal outcomes of emergency cerclage were similar to those of elective cerclage.